Impact of Photovoltaic Penetration on Medium Voltage Distribution Network - Maghami M.R.; Pasupuleti J.; Ling C.M. (MDPI, 2024)
Nowadays, large-scale solar penetration into the grid and the intermittent nature of PV systems are affecting the operation of distribution networks. This paper aims to investigate the effect of PV penetration on a typical medium-voltage distribution network in Malaysia. The main objectives of this study are to investigate voltage stability, power loss, and short circuit under two conditions: peak load and no load. The network is evaluated using two methods: static and dynamic analysis, utilizing the Digsilent Power Factory software. The network comprises two 33/11 kV parallel transformers connected to the 11 kV busbar and consists of 13 feeders and 38 loads. PV penetration of 500 kW per node is added, and the maximum potential PV penetration that is acceptable to connect to the grid is evaluated. The findings indicate that during peak load conditions, some nodes experience violations, but by increasing the PV penetration, the lower violations move up to the acceptable range. The highest power loss is 191 kW, occurring during peak load conditions at 0% PV penetration level. On the other hand, dynamic simulations were carried out with specific load time characteristics, and the results were compared under different PV penetration levels. The dynamic simulation results show that during contingency conditions, there are violations in peak load, and the maximum PV penetration for this study was determined to be 2MW. It is observed that the nodes 27, 28, and 29 violate lower voltage limits even at 100% PV penetrations. 2023 by the authors.